Strategic decisional beliefs: Conceptualization and empirical research - Bilson Simamora (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2021)
Extant studies hold that the decision quality at the very moment of choice indicates future task accomplishment. However, regarding individual-making, the decision’s strategic nature still received little attention from scientists so far. For that reason, the author utilizes the strategic decision dimensions of justifiability, confidence, and satisfaction to form a new concept called strategic decisional beliefs. Making self-efficacy, motivation, subjective well-being, loyalty, and switching likelihood as the concept’s consequences under investigation, the author tests the concept using data from 350 new students chosen judgmentally. As expected, exploratory factor analysis with maximum likelihood extraction offers only one latent variable for the three underlined dimensions. Further investigation with confirmatory factor analysis indicates that all items are internally valid, reliable, and solidly merged into a single construct with a close fit measurement model. Good-fit structural equation modeling with Lisrel 8.8 successfully confirms that strategic decisional beliefs predict the specified consequences strongly. Interestingly, the construct has better structural validity in a unidimensional than a multidimensional form. This study still relies on a single cross-sectional design. Hopefully, further research can utilize a longitudinal design to investigate how strategic decisional beliefs predict individuals’ actual performance, satisfaction, and loyalty. Original Article | Turnitin